Analisis Risiko dan Perilaku Pencegahan Penyakit DM Tipe 2 pada Usia Produktif di Wilayah Kerja UPTD Puskesmas Depok Jaya Tahun 2022: Risk Analysis and Prevention Behavior for Type 2 DM in the Productive Age in the Depok Jaya Community Health Center UPTD Work Area in 2022 - Listriyani, Ayu Suranti; Sandya, Felix; Handayani, Mega Indah; Leftungun, Stefani Yulita (MPI Press, 2023)
Background: Diabetes is a non-communicable disease that must be treated, Diabetes Mellitus (DM) is a metabolic disease characterized by high blood sugar levels. Indonesia is one of the countries with the highest number of diabetes cases in the world and occupies the fifth position with the number of people with diabetes in 2019 from 10.7 million people to 19.5 million people in 2021. For the West Java region in 2019, the prevalence of diabetes was 16 0.03%, and in 2020 there was an increase in cases to 24.39%. Objectives: To find out the risk factors and preventive behavior of type 2 DM at productive age in the working area of ​​the UPTD Puskesmas Depok Jaya in 2022 Method: The population of this study was the people in the area. The work of UPTD Puskesmas Depok Jaya suffering from diabetes mellitus with a sample of 90 respondents who filled out an online questionnaire using a google form. This research was conducted in April-August 2022, with this type of research being descriptive qualitative research using primary data from observations using an online questionnaire (google form) and secondary data taken from the health profile of the Depok Jaya Health Center 2022. Result: Based on the results of risk factors with genetic aspects of diabetes mellitus, it is ranked 3rd with a total of 22 (24%) respondents from 10 hereditary diseases. Based on risk factors with diabetes mellitus prevention behavior: physical activity from 90 respondents obtained 75 (83.3%) with indicators of doing physical activity every day. While the aspect with the lowest coverage value is that there are still family members who smoke (especially in the house), namely 49 (54.4%), eat fruit and vegetables every day, namely 56 (62.2%) respondents. Based on the characteristics of the aspect of health services, almost all Depok Jaya people use puskesmas facilities as much as 94.4%. Conducting periodic health checks as many as 74 (82.2) respondents Conclusions: Of the 10 highest diseases, diabetes mellitus is ranked 3rd with a total of 8 (10%). Based on this analysis, the incidence of diabetes mellitus is quite high with the presence of risk factors, unhealthy lifestyles and the lack of respondents to go to health services.